Anxiety and Its Effects on Listening and Speaking Achievements of Engineering Students - Sri Endah Kusmartini (Politeknik Negeri Sriwijaya, 2021)
The study investigated the anxiety and its effects on listening and speaking achievement of engineering students, Sriwijaya State Polytechnic. It was quantitative research. The samples were 109 students of the electrical engineering study program. The researcher used Foreign Language Classroom Anxiety Scale with some adaptation to collect the data about anxiety and took the data about the listening and speaking achievements of the students from listening and speaking tests. The researcher used descriptive statistics, Pearson Product Moment Coefficient Correlation, and linear regression to analyze the data. The negative correlation between student foreign language classroom anxiety and the listening achievement of the students was significant. Next, student foreign language classroom anxiety also correlated negatively towards student speaking achievement. Finally, there were some contributions of foreign language classroom anxiety towards student listening and speaking achievements. Keywords: Foreign language classroom anxiety, listening, speaking